Accreditation of the GHEP-ISFG proficiency test: One step forward to assure and improve quality. (December 2015) - Fernández, K.; Gómez, J.; García-Hirschfeld, J.; Cubillo, E.; de la Torre, C.Sánchez; Vallejo, G.
Abstract: Since 1992, it has been organized annually in Spain, a Forensic Intercomparison Exercise coordinated by the Madrid Department of the National Institute of Toxicology and Forensic Sciences (INTCFM) and organized by the Spanish and Portuguese Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG). The need to improve and assure the quality of our services as well as to demonstrate our competence, led us to accredit this Exercise under ISO/IEC 17043. This International Standard ensures quality of proficiency testing providers regarding technical and management requirements. In this work, we present the step-wise process we began in 2011 focused on upgrading the Basic level of the Intercomparison Exercise towards its accreditation, which was successfully achieved in December 2014. All adjustments made are described. From the early structural changes, since the Exercise had to be divided in two levels, passing through the definition of the scope, to the technical improvements made and management policy implementation.